Vascularized Osseous Flaps and Assessing Their Bipartate Perfusion Pattern via Intraoperative Fluorescence Angiography - Valerio, Ian; Green, J. Marshall, III; Sacks, Justin M.; Thomas, Shane; Sabino, Jennifer; Acarturk, T. Oguz (Journal of Reconstructive Microsurgery, 2015)
Background Large segmental bone and composite tissue defects often require vascularized osseous flaps for definitive reconstruction. However, failed osseous flaps due to inadequate perfusion can lead to significant morbidity. Utilization of indocyanine green (ICG) fluorescence angiography has been previously shown to reliably assess soft tissue perfusion. Our group will outline the application of this useful intraoperative tool in evaluating the perfusion of vascularized osseous flaps.Methods A retrospective review was performed to identify those osseous and/or osteocutaneous bone flaps, where ICG angiography was employed. Data analyzed included flap types, success and failure rates, and perfusion-related complications. All osseous flaps were evaluated by ICG angiography to confirm periosteal and endosteal perfusion.Results Overall 16 osseous free flaps utilizing intraoperative ICG angiography to assess vascularized osseous constructs were performed over a 3-year period. The flaps consisted of the following: nine osteocutaneous fibulas, two osseous-only fibulas, two scapular/parascapular with scapula bone, two quadricep-based muscle flaps, containing a vascularized femoral bone component, and one osteocutaneous fibula revision. All flap reconstructions were successful with the only perfusion-related complication being a case of delayed partial skin flap loss.Conclusions Intraoperative fluorescence angiography is a useful adjunctive tool that can aid in flap design through angiosome mapping and can also assess flap perfusion, vascular pedicle flow, tissue perfusion before flap harvest, and flap perfusion after flap inset. Our group has successfully extended the application of this intraoperative tool to assess vascularized osseous flaps in an effort to reduce adverse outcomes related to preventable perfusion-related complications.
Keywords: intraoperative angiography; osseous; perfusion